Pengembangan Video Pembelajaran Berbasis Pendekatan Saintifik Etnosains pada Materi Zat Tunggal dan Campuran - Fadilah, Khumiyati; Trisnawati, Eka (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2022)
This study aims to develop a learning video based on the scientific approach of ethnoscience on single and mixed substances that is feasible and effective on the learning motivation. This research is research and development (R&D) method with a 4D development design. The subjects of this research were media experts, material experts, and fifth grade students of SD Negeri 3 Pekuncen for the 2020/2021 Academic Year. Data collection techniques used interviews, object study expert assessment questionnaires, media learning expert assessment questionnaires, learning motivation questionnaires, and learning implementation observations. The data analysis technique used quantitative descriptive analysis and hypothesis testing using simple linear regression. The results of the learning media expert assessment were 90% (very feasible), while the results of the material expert assessment were 82.50% (very feasible). The results of the regression analysis obtained the value of F count > F table, which is 27,176 > 4,965. In conclusion, the learning video based on the scientific approach of ethnoscience on single substance and mixed substance development results was feasible and effective in influencing learning motivation for grade V Elementary School.